1995
DOI: 10.1111/j.1399-302x.1995.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and characterization of plasmids in oral anaerobic spirochetes

Abstract: Fifteen oral spirochete strains belonging to the species Treponema denticola, Treponema vencentii and Treponema socranskii as well as 9 fresh clinical isolates were screened for the presence of extrachromosomal plasmid DNA by a modified alkaline lysis procedure. A 2.6-kb plasmid was detected in both T. denticola ATCC 33520 and T. denticola e'. The 2.6-kb plasmid from T. denticola e' was shown to be similar to pTD1, previously reported by Ivic et al. in T. denticola ATCC 33520 on the basis of molecular weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Taken together, the phenotypic and genetic properties of the isolates suggest that U2a and U2b are strains of T. soeranskii while U9b and U9c are strains of T. dentieola. The presence of the same 4.2-kb plasmid in different species of Treponema reinforces the suggestion of a possible naturally occurring genetic transfer system within the periopathic treponemes (1) or their ability to take up and maintain mobilizable plasmids, especially when strains U2b and U9c were isolated from the same patient. Since this plasmid is the first one described in T. socratiskii, the designation "pTSl" is given to the 4.2kb plasmid.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Taken together, the phenotypic and genetic properties of the isolates suggest that U2a and U2b are strains of T. soeranskii while U9b and U9c are strains of T. dentieola. The presence of the same 4.2-kb plasmid in different species of Treponema reinforces the suggestion of a possible naturally occurring genetic transfer system within the periopathic treponemes (1) or their ability to take up and maintain mobilizable plasmids, especially when strains U2b and U9c were isolated from the same patient. Since this plasmid is the first one described in T. socratiskii, the designation "pTSl" is given to the 4.2kb plasmid.…”
supporting
confidence: 73%
“…The isolation of two further plasmids (7), both from T. dentieola, suggests that this species in vivo can acquire and maintain transferrable plasmids, a process that may contribute to their virulence in pedodontal disease. In a previous study, we investigated the presence of plasmids in clinical isolates of other Treponema species and determined whether such plasmids were similar to those isolated from T. dentieola (1). Screening for the presence of plasmids was carded out on nine pure strains of clinical isolates of spirochetes from pedodontal pockets.…”
mentioning
confidence: 99%
“…To prepare methylated pBFC, the plasmid was transformed into E. coli TOP10, which contains the dam gene encoding a DNA methyltransferase that methylates the N 6 position of the adenine residues in the sequence GATC (18,20). To prepare unmethylated CACTATCTAATATGAACAAAAATATAAAATATTCTC ermB cassette; F P 4 CCAGATTTTTTTTATTTCCTCCCGTTAAATAATAG ermB cassette; R P 5 GAGGAAATAAAAAAAATCTGGATTTGTGTATGT 3Ј-flanking region of TDE0911; F P 6 CACACGTAAAACAGATGAC 3Ј-flanking region of TDE0911; R P 7 CTAATCAACAAATAATACAGGTC TDE0911 probe; F P 8 CTATCTATGCTGTGCAAAATAG TDE0911probe; R P 9 CGAATGAAAAGGTACTCAACC ermB probe; F P 10 CCTCCCGTTAAATAATAG ermB probe; R P 11 CCAAATGATGCTTATGTTGC TDE0228 probe; F P 12 CCAAGTAAATTCTTGTTGCT TDE0228 probe; R P 13 CTCAGATAGTAAGGGTGT TDE1268 probe; F P 14 GGAGTTGTTGTCTTATCT TDE1268 probe; R P 15 GCACATGTAGGCTCAGCCCTGACCAAGTC aacC1 site mutagenesis; F P 16 GACTTGGTCAGGGCTGAGCCTACATGTGC aacC1site mutagenesis; R P 17 ATGTTACGCAGCAGCAACG aacC1 cassette; F P 18 TTAGGTGGCGGTACTTGGG aacC1cassette; R P 19 GAGCAACCAGAAATTGTTC 3Ј-flanking region of P 6 ; R a Underlined portions show the engineered overlapping base pairs. b Primer orientation: F, forward; R, reverse.…”
Section: Methodsmentioning
confidence: 99%
“…However, these two strains possess many physiological and genetic differences, such as serotype (7,8), oxygen tolerance (46), and biofilm formation capability (24,48,49). In addition, four plasmids have been isolated from several oral treponemes, including ATCC 33520, but none of these plasmids has been isolated from ATCC 35405 (4,5). Moreover, three shuttle vectors (pKMR4PE, pKMCou, and pBFC) that were derived from the plasmid pTS1 have been successfully transferred into ATCC 33520 but not ATCC 35405 (5,9,10,44).…”
mentioning
confidence: 99%
“…We compared the 3 plasmids of T. denticola by size, restriction mapping, regions of homology, and presence of ssDNA. Recently, Caudry et al (5) have reported a 2.6-kb pTDl-like plasmid in 77 denticola clinical isolate e'.…”
mentioning
confidence: 99%